2006
DOI: 10.1590/s0101-20612006000300027
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da contaminação com aflatoxina entre embalagens de produtos de amendoim

Abstract: resumoEste estudo foi realizado com o objetivo de avaliar o perfil da distribuição da contaminação com aflatoxinas entre embalagens constituintes de lotes de confeitos de amendoim, expostos à venda no comércio. Os dados da distribuição da ocorrência e dos níveis de contaminação, aqui obtidos, sugerem que os procedimentos de amostragem, visando à detecção de aflatoxinas em produtos processados, sempre estarão associando um grau de incerteza muito elevado quanto à presença ou não e quanto ao nível médio de conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…However, corn and peanut, as well as corn and peanut-based products are the main foods related to aflatoxin contamination (Caldas, Silva, & Oliveira, 2002;Gloria, Fonseca, & Souza, 1997;Gloria, Romero, Carvalho, Calori-Domingues, & Gonçalves, 2006;Kawashima & Valente-Soares, 2006;Rodriguez-Amaya & Sabino, 2002;Sabino et al, 2000). Milk and dairy products are also frequently reported as contaminated in Brazil with low aflatoxin levels (Gonçalez et al, 2005;Oliveira & Ferraz, 2007;Oliveira, Germano, Bird, & Pinto, 1997); Oliveira, Rosmaninho, & Rosim, 2006;Shundo & Sabino, 2006. However, there are few investigations on the presence of aflatoxin exposure biomarkers in the Brazilian population.…”
Section: Introductionmentioning
confidence: 99%
“…However, corn and peanut, as well as corn and peanut-based products are the main foods related to aflatoxin contamination (Caldas, Silva, & Oliveira, 2002;Gloria, Fonseca, & Souza, 1997;Gloria, Romero, Carvalho, Calori-Domingues, & Gonçalves, 2006;Kawashima & Valente-Soares, 2006;Rodriguez-Amaya & Sabino, 2002;Sabino et al, 2000). Milk and dairy products are also frequently reported as contaminated in Brazil with low aflatoxin levels (Gonçalez et al, 2005;Oliveira & Ferraz, 2007;Oliveira, Germano, Bird, & Pinto, 1997); Oliveira, Rosmaninho, & Rosim, 2006;Shundo & Sabino, 2006. However, there are few investigations on the presence of aflatoxin exposure biomarkers in the Brazilian population.…”
Section: Introductionmentioning
confidence: 99%
“…CCPP 6 refers to the packed final product, which must not be contaminated by aflatoxins, toxigenic fungi, and spores or stored under conditions that would favour spore development (Gloria et al. , 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Mycotoxin contamination in food occurs because of certain events and circumstances along the production chain of the agricultural product. Studies in Brazil have shown a high occurrence of aflatoxins in groundnut and groundnut-derived products, and when ingested, the toxins are a hazard to consumers' health (Sabino et al, 1982(Sabino et al, , 1989Prado et al, 1989;Santos et al, 2001;Caldas et al, 2002;Rodriguez-Amaya & Sabino, 2002;Gloria et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos realizados no Brasil demonstram que os produtos derivados de milho e amendoim são altamente implicados em casos de ocorrência de micotoxinas, especialmente com relação à ocorrência de aflatoxinas (VALE, 1992;GLORIA et al, 1997;FONSECA et al;1998;SILVA, 2000;FARIAS et al, 2000;MACHINSKY JUNIOR et al, 2001;SANTOS et al, 2001;BITTENCOURT, 2002;CALDAS et al, 2002;KAWASHIMA, 2004;GLORIA et al, 2006). Vale (1992) analisaram a presença de aflatoxina B 1 em 70 amostras de milho pipoca coletadas na cidade de Fortaleza e provenientes, em sua maioria, do Estado do Ceará.…”
Section: Ocorrência De Aflatoxinas Em Alimentosunclassified
“…Inúmeros trabalhos relatam à ocorrência de aflatoxinas em milho in natura e em fubá e farinha, entretanto, a contaminação também pode ocorrer em outros produtos processados à base de milho, tais como curau, polenta pronta e pré-cozida, quirera, canjica e canjiquinha, pipoca, flocos de milho, pipoca açucarada e salgadinho (AMARAL et al, 2006;KAWASHIMA;SOARES, 2006), em concentrações que variam de valores inferiores a 1 μg/kg até 20 μg/kg. Fonseca et al (1998) Gloria et al (2006) analisaram amostras de produtos derivados de amendoim comercializados na cidade de Piracicaba-SP e constataram contaminação em 25% das 297 amostras. A concentração da contaminação por aflatoxinas esteve entre 1 e 346 μg/kg em produtos como amendoim japonês, ovinhos de amendoim, doces de amendoim e paçoca.…”
Section: Ocorrência De Aflatoxinas Em Alimentosunclassified